Ungendering civilization - Pyburn, K. Anne (Routledge, 2004)
Ungendering Civilization offers a much needed scrutiny of the role of women in the evolution of states. The contributors critically address traditional views of male and female roles; they argue for the possibility that the root historical cause of gender subordination is participation in modern world system, rather than 'innate' tendencies to domesticity and child-rearing in women, and leadership and aggression in men. Each of the nine papers examines a distinct body of archaeological data - from societies including Predynastic Egypt, Minoan Crete, ancient Zimbabwe and the Maya - to determi.